DSR and OLSR routing protocol based performance evaluation and integration on MIP with MANET - Sirajum Munira; Humaira Sadia; Samara Fahin; Ashraf Siddik; A.K.M. Fazlul Haque (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper describes the integration of mobile IP in mobile ad hoc network (MIPMANET) in large area network (LAN) between 8 nodes, where latency, delay, throughput is considered for the quality of service (QoS) consideration. For the best result of MIPMANET, the Dynamic Source Routing Protocol (DSR) and Optimized Link State Routing Protocol (OLSR) are considered. Although MANET has other routing protocols, the DSR performs better in MIPMANET integration in NS2. Mobile IP is applied for doing the dynamic topology to static topology as the nodes are flexible in an ad-hoc network. Simulation result suggests that the MANET performs better in DSR with MIP as the amount of packet drop is low and throughput is high